1999
DOI: 10.1148/radiology.213.2.r99nv26481
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Cancer: Prediction of Extracapsular Extension with Endorectal MR Imaging and Three-dimensional Proton MR Spectroscopic Imaging

Abstract: The addition of 3D MR spectroscopic imaging to MR imaging improves accuracy for less experienced readers and reduces interobserver variability in the diagnosis of ECE of prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
176
1
11

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 323 publications
(194 citation statements)
references
References 42 publications
6
176
1
11
Order By: Relevance
“…This result may have been related to the experience levels of the two readers, which were roughly equivalent: Both readers had read more than 1000 prostate MR studies before taking part in this investigation. Previous study investigators have found that using MR spectroscopic imaging increases reader confidence and significantly improves reader performance in the interpretation of MR imagesespecially that of less experienced readers (33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…This result may have been related to the experience levels of the two readers, which were roughly equivalent: Both readers had read more than 1000 prostate MR studies before taking part in this investigation. Previous study investigators have found that using MR spectroscopic imaging increases reader confidence and significantly improves reader performance in the interpretation of MR imagesespecially that of less experienced readers (33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…One study reported that adding DCEI to T2WI for T-staging resulted in a sensitivity of 86% and specificity of 95% for detecting EPE [112]. Another study failed to validate these findings [113], however, and two studies reported that combining MRS and T2WI failed to improve accuracy over T2WI alone in staging [114,115].…”
Section: Mri In T-staging Treatment Selection and Planningmentioning
confidence: 99%
“…One recent study reported an overall staging accuracy of 93% and 56% for two different readers within the same study (28). Although inter-reader variability can be due to differences in reader experience and subjectivity, the addition of objective metabolic criteria provided by MRSI has been demonstrated to decrease this inter-reader variability (29).…”
Section: Morphologic Identification Of Prostate Cancer-mrimentioning
confidence: 99%
“…This study was based on prior histopathologic studies that demonstrated that tumor volume was a significant predictor of extracapsular extension (ECE) of prostate cancer (75,76). It was found that tumor volume per lobe estimated by MRSI was significantly (P Ͻ 0.01) higher in patients with ECE (2.14 Ϯ 2.3 cm 3 ) than in patients without ECE (0.98 Ϯ 1.1 cm 3 ) (29). Moreover the addition of an MRSI estimate of tumor volume to high-specificity MRI findings for ECE (74) improved the diagnostic accuracy and decreased the inter-observer variability of MRI in the diagnosis of extracapsular extension of prostate cancer (Fig.…”
Section: Improved Prostate Cancer Staging Using Combined Mri/mrsimentioning
confidence: 99%